Pengaruh Komik “PUSAR: Perubahan Saat Remaja” Terhadap Pengetahuan dan Kesiapan Menghadapi Pubertas. - Hanifa, Sifa (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: To assess the impact of the comic media "PUSAR: Perubahan Saat Remaja" on adolescents' knowledge and readiness to face puberty Methods: This study employs a quantitative approach with a quasi-experimental design, specifically a pretest-posttest with a control design. The respondents included seventh-grade students from MTs Ushriyyah Purbalingga and MTs Muhammadiyah 1 Purbalingga, comprising 48 participants in the intervention group and 48 participants in the control group, selected using purposive sampling. The Whitney-Mann Test was used for statistical analysis. Results: Bivariate analysis using the Whitney Mann Test compared the mean data between the intervention and control groups. The mean knowledge score yielded a p-value of 0.000, indicating statistical significance (p 0.05), while the mean readiness score showed a p-value of 0.037, also indicating significance (p 0.05). Conclusion: The comic media "PUSAR: Perubahan Saat Remaja" significantly influences adolescents' knowledge and readiness to face puberty.